1961
DOI: 10.1002/jsfa.2740121111
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the oxidative deterioration of the lipids of crude leaf protein

Abstract: Measurements of oxygen absorption have been carried out on a sample of crude leaf protein, containing about 20% lipid, at temperatures between 37' and -1 2 ' and pH 26-6.0.An enzyme system was active in the moist but not in the freeze-dried product. Attempts to protect the lipid of the freeze-dried protein by the addition of antioxidants were unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…of lipids and the fatty acids in them are highly unsaturated (Lima et al. 1965) and readily undergo oxidation (Lea and Parr 1961); this increases the ''leafy'' flavour. The lipids, including chlorophyll and its breakdown products can easily be extracted with solvents.…”
Section: Rothamstead Experimental Station Harpendenmentioning
confidence: 99%
“…of lipids and the fatty acids in them are highly unsaturated (Lima et al. 1965) and readily undergo oxidation (Lea and Parr 1961); this increases the ''leafy'' flavour. The lipids, including chlorophyll and its breakdown products can easily be extracted with solvents.…”
Section: Rothamstead Experimental Station Harpendenmentioning
confidence: 99%
“…The fishy off‐flavor is probably associated with TMA. It has been reported that fishy odor was detected in leaf protein containing a high amount of galactolipids or phospholipids (Lea and Parr 1961). Fishy off‐flavor has been detected in dry spinach stored in nitrogen at low temperatures (Masanetz and others 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although LPC has been shown to have a favorable balance of essential amino acids (Betschart and Kinsella, 1974a;Byers, 1971;Gerloff et al, 1965) and has been effectively used as a suppplement for human and animal diets (Doraiswamy et al, 1969;Waterlow, 1962;Woodham, 1971), there are problems associated with this potentially valuable source of protein. The presence of "grassy, hay-like" odors and flavors in stored LPC is one such problem (Protein Advisory Group, 1970;Lea and Parr, 1961;Shah, 1968). These undesirable organoleptic qualities have been associated with the oxidation of the lipid fraction of LPC (Buchanan, 1969a;Kohler and Bickoff, 1970;Lea and Parr, 1961).…”
Section: Introduction Leaf Protein Concentratementioning
confidence: 99%
“…The presence of "grassy, hay-like" odors and flavors in stored LPC is one such problem (Protein Advisory Group, 1970;Lea and Parr, 1961;Shah, 1968). These undesirable organoleptic qualities have been associated with the oxidation of the lipid fraction of LPC (Buchanan, 1969a;Kohler and Bickoff, 1970;Lea and Parr, 1961).…”
Section: Introduction Leaf Protein Concentratementioning
confidence: 99%
See 1 more Smart Citation